A Hydroalcoholic Extract from Paullinia pinnata L. Roots Exerts Anthelmintic Activity against Free-Living and Parasitic Nematodes - Spiegler, Verena; Liebau, Eva; Peppler, Carolin; Raue, Katharina; Werne, Steffen; Strube, Christina; Heckendorn, Felix; Agyare, Christian; Stark, Timo; Hofmann, Thomas; Hensel, Andreas (Planta Medica, 2016)
Paullinia pinnata is a medicinal plant traditionally used in West Africa against a wide range of diseases including soil-transmitted helminthiases. In this study, a hydroethanolic root extract was investigated for its phytochemical composition and in vitro activity against the free-living nematode Caenorhabditis elegans as well as the larval stages of the parasitic helminths Ancylostoma caninum, Haemonchus contortus, Toxocara cati, and Trichuris vulpis.LC-MS analysis of the ethanol-water (1 : 1) extract revealed epicatechin and different A-type linked oligomeric and polymeric procyanidins as the predominant compounds.Within an in vitro mortality assay, the extract showed a lethal activity against T. cati (LC50 of 112 µg/mL), T. vulpis (LC50 of 17 µg/mL), and C. elegans (LC50 2.5 of mg/mL), but not against A. caninum. Additionally, effects on egg hatching and larval migration of H. contortus were investigated, but no inhibitory activity was observed.Overall, these findings rationalize the traditional use of the root extract from P. pinnata as an anthelmintic remedy and provide insight into the phytochemical composition of the extract.
Keywords: Paullinia pinnata; Sapindaceae; A-type procyanidin; Caenorhabditis elegans; Toxocara cati; Trichuris vulpis; Ancylostoma caninum; Haemonchus contortus